A Flexible Programming and Verification Methodology for Reconfigurable CNC Woodworking Machine - Sasa Zivanovic; Zoran Dimic; Mladen Furtula; Nikola Slavkovic; Marija Djurkovic; Jelena Vidakovic (BioResources)
An advanced flexible programming methodology for CNC woodworking machines was developed. As the research starting base, a three-axis CNC woodworking machine was used. The developed methodology is proposed for programming, simulation, postprocessing, and machining by woodworking machine. This flexible programming method integrates the standard programming based on CAD, CAD/CAM systems, and STEP-NC protocol through different output files, enabling data interoperability during the realization of the machining tasks. The control system for the machine is configured based on the open-architecture software LinuxCNC to verify the flexible programming method and the results obtained. Programming verification was realized by simulation on a configured virtual machine in different programming environments and finally on a virtual machine integrated with the control system. The results obtained from the study were evaluated comparatively.